Primeval very low-mass stars and brown dwarfs: IV. New L subdwarfs, Gaia astrometry, population properties, and a blue brown dwarf binary - Zhang, Zeng Hua; Homeier, Derek (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. We present 27 new L subdwarfs and classify five of them as esdL and 22 as sdL. Our L subdwarf candidates were selected with the UKIRT Infrared Deep S